Government Ownership and Non-Performing Loans: Evidence from Indonesia Banks - Agustin, Hamdi; Mardianty, Desy; Azwirman (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia bank institutions have three form of ownership structure. There are private, government and community development banks. One of the unique banking in Indonesia is that there are community development bank (CDB), which is a government-owned bank districts. This research investigates the effect ownership structure on the nonperforming loans of Indonesia banks.The data used in this research is secondary data with reference to all the Bank in Indonesia for the period 2008-2013. Total population of the study was 124 banks from 2008 up to the period of 2013. Sampling was done by purposive sampling method which gained 45 national private banks, 22 CDB and 4 government banks. The results showed that there are different variables NPL, CAR, LDR and ROA of individual ownership of national private banks, CDB and government bank. ROA and LDR have a significant effect on the NPL. One thing that is very interesting in this study is the ownership dummy CDB positive effect on the NPLs, it indicates that the CDB had a large level of non-performing loans compared to private and government banks.